How Numerical Unbalance Constraints Physical and Tactical Individual Demands of Ball Possession Small-Sided Soccer Games - Nunes, Nuno (2020)
This study aimed to explore the effects of playing different unbalanced ball possession small-sided games on external workload (distance covered while walking, running, and sprinting, and max speed), tactical individual actions (number of passes with dominant and non-dominant foot), and internal load (rating of perceived exertion, RPE) in under-23 soccer players. Participants played 4v2, 4v3, 4v4, 4v5, and 4v6 small-sided games (SSGs) on a 30 × 25 m playing area. Data were analyzed under an opponent-based perspective, by fixing one team (4vX), and by cooperation-based perspective according to teammates (4v2+X). Global Position System (GPS) monitors were used to collect and compute external workloads and individual tactical actions, and Borg Scale CR10 was used to evaluate RPE. High-Superiority (4v2), Superiority (4v3), and Very Low-Cooperation (4v2+0) formats allow players in balanced teams to cover more distance while walking; on the other side, Inferiority (4v5), High-Inferiority (4v6), and Very High-Cooperation (4v2+4) allow players to sprint more and practice more tactical individual actions as a resultant emergent behavior; all players in SSG conditions with a lower number of conditions, perceived the exercise as more intense, especially in situations with less than two players. Overall, playing in high inferiority situations (4v2 and 4v6) may be used to increase physical demand for the outnumbered team, while coaches may use low superiority situations to adjust the task complexity when developing the players’ tactical individual actions.